2020
DOI: 10.15240/tul/001/2020-4-010
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Financial Stress Shocks between the USA and the Euro Area During Different Business Cycle Phases

Abstract: This paper examines the transmission of financial stress shocks between the USA and the euro area for recessionary and non-recessionary regimes in the shock-recipient economy. The investigated period is 1999M1–2017M11, which includes several episodes of recessionary and non-recessionary regimes, endogenously determined by the model, as well as several financial stress episodes. After testing for non-linearity, we employ a five-variable Bayesian threshold vector autoregression model using internationally compat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…In contrast, Dajčman et al (2020) found that systemic stress negatively affects industrial production in the euro area in recessionary and non-recessionary regimes.…”
Section: The Impact Of Systemic Stress On the (Real) Economymentioning
confidence: 88%
See 2 more Smart Citations
“…In contrast, Dajčman et al (2020) found that systemic stress negatively affects industrial production in the euro area in recessionary and non-recessionary regimes.…”
Section: The Impact Of Systemic Stress On the (Real) Economymentioning
confidence: 88%
“…The body of evidence on the impact of systemic stress on the (real) economy is more limited than for the financial stress. In this subsection, I focus on studies that use the CISS (see Chatterjee idr., 2017;Chavleishvili & Kremer, 2017;Chavleishvili & Manganelli, 2019;Dajčman et al, 2020;Hartmann et al, 2013;Holló et al, 2012;Kremer, 2016a;Silvestrini & Zaghini, 2015). Holló et al (2012) and Kremer (2016a) D. Romih: The Impact of Systemic Stress in the Euro Area on Bilateral Exports of Goods studied the impact of systemic stress on industrial production in the euro area.…”
Section: The Impact Of Systemic Stress On the (Real) Economymentioning
confidence: 99%
See 1 more Smart Citation
“…Cushman and Zha (1997) point out that U.S. monetary policy shocks have a greater spillover effect on other countries' macroeconomies compared to other central countries' policy adjustments. Daj cman et al (2020) suggest that U.S. financial stress shocks negatively affect euro area macroeconomy. Albagli et al (2019) suggest that compared to other events, the U.S. monetary policy shocks have at least the same amount of spillover impact as the domestic monetary policy after the postglobal financial crisis.…”
Section: Introductionmentioning
confidence: 99%
“…This means that when a systemic financial crisis occurs, the functioning of the financial system is disrupted. Research has shown that systemic stress negatively affects the economy (see Chavleishvili & Manganelli, 2019;Dajčman et al, 2020;Kremer, 2016a). As a result, there is a growing need among policymakers and researchers at central banks to measure and monitor systemic stress.…”
Section: Introductionmentioning
confidence: 99%